GENERASI Z DAN KEMANDIRIAN FINANSIAL? PERAN FRUGAL LIVING DAN LITERASI KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN DENGAN GENDER SEBAGAI VARIABEL PEMODERASI - Astungkara, Agni; Ciptaningtias, Arum Febriyanti; Mahesti, Triloka (ITB AAS INDONESIA, 2024)
In a dynamic economy, the ability to survive is essential. One strategy to survive is to have financial independence. Financial independence can be achieved with good financial management. This study examines the effect of frugal lifestyle (frugal living), financial literacy, and gender on financial management behavior. The sample of this research is 88 students at a state university in Semarang city. With regression analysis techniques, this study shows the results that frugal living and financial literacy have a significant positive effect on financial management behavior. Gender variables are also able to moderate the influence of frugal living and financial literacy on financial management behavior. This research is presented to be able to encourage generation Z in conducting financial management as an effort to achieve financial independence.